The Existence of the Atib Koambai Cultural Tradition in the Babussalam Rokan Hilir Community - Camelia Khuznul Ma’wa; Hambali Hambali; Jumili Arianto (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This research is motivated by the existence of the Atib Koambai cultural tradition in the village of Teluk Nilap, Kubu Babussalam District, regarding the Existence of the Atib Koambai Cultural Tradition. The formulation of the problem of this research is what is the background of the birth of the Atib Koambai tradition and what are the factors that influence the Babussalam community to carry out the Atib Koambai tradition and how is the existence of the Atib Koambai tradition in the Babussalam community, Rokan Hilir Regency. The purpose of this study is to find out and analyze the historical background and how the existence of the Atib Koambai cultural tradition in the Babussalam Community, Rokan Hilir Regency. Data collection techniques in this study are observation, interviews and documentation. The informants in this study consisted of the people of Kubu Babussalam District, namely 4 people from traditional leaders / Tuan Kholifah, Ustadz and and young people (3 people). Data analysis techniques in this study used qualitative methods with a descriptive approach. The findings in this study explain that the existence of the Atib Koambai cultural tradition is still carried out today but has experienced shifts or changes such as in the field of transportation, implementation procedures, and people's understanding of the Atib Koambai tradition in Teluk Nilap village, Kubu Babussalam sub-district, Rokan Hilir due to a lack of the public's interest in participating in the implementation of the Atib Koambai cultural tradition so that it can cause the loss or extinction of the existence of the Atib Koambai cultural tradition in the Babussalam stronghold community.